If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 + -1z = 15 Solving 9 + -1z = 15 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + -1z = 15 + -9 Combine like terms: 9 + -9 = 0 0 + -1z = 15 + -9 -1z = 15 + -9 Combine like terms: 15 + -9 = 6 -1z = 6 Divide each side by '-1'. z = -6 Simplifying z = -6
| 24a^2-46a-18=0 | | 3-2.7(8-x)=15.16 | | 700000000/100 | | 7000000000/20000 | | 6a^2-14a-12=0 | | 10t-7=25 | | a=p(l+rt) | | -3/13p=4 | | 7x+2x-3=0 | | 13/5+23/4 | | 4y^2-16y=0 | | x/2+3=2x+7 | | 4y^2-16y+12=0 | | 3x+9y=-21 | | 8x-72=4x-12 | | -x+9=13 | | 500-2x=4x+100 | | p=-x^2+68x+84 | | -64/16x | | 8(t-4)+6t=7(2t+5)-12 | | x/2+1=2x/5-2 | | 6597=.08x+.05y | | 7x+y+y+2z-5x-y= | | 2(x+1)-10=-5(x+2) | | -(6y+1)-(-5y-8)=2 | | 0.3x+0.5=1 | | 4x+11-6x=14-16x+14x-3 | | 14x-13=11x-2 | | 3x+3-6x+6-9x-9=12-12x+15x+18+27 | | 5/6*-1/5x+4=7/10x | | 5x-41=3x-11 | | 0=-6x-4x+5 |